2015
DOI: 10.1016/j.rmed.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium and not vitamin D is associated with better QoL in COPD: A cross-sectional study

Abstract: Serum levels of vitD, Mg and Ca were not related to FEV1. Most participants in this study were vitD-, Mg- and Ca sufficient. Women had higher se vitD than men. Se Mg, but not se vitD and se Ca, was associated with QoL in COPD. Prospective randomized studies are needed to substantiate these finding. Clinical trials ID at www.clinicaltrials.gov: NCT01564953.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 25 These results are in agreement with other studies confirming low levels of D vitamin in COPD patients. 26 , 27 According to our data, ACOS patients had better lung function parameters and mMRC scores than COPD patients, suggesting that their overall functional status may, perhaps, be better. As compared to the healthy population, ACOS patients also have decreased exercise performance, which may play an important role in the detection of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 56%
“… 25 These results are in agreement with other studies confirming low levels of D vitamin in COPD patients. 26 , 27 According to our data, ACOS patients had better lung function parameters and mMRC scores than COPD patients, suggesting that their overall functional status may, perhaps, be better. As compared to the healthy population, ACOS patients also have decreased exercise performance, which may play an important role in the detection of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, both COPD and COVID‐19 reduce mediators that promote vasodilation such as endothelial nitric oxide synthase (eNOS) 28,30,38,136‐141 . It has been demonstrated that COPD severity was associated with serum Mg 2+ deficiency and a worse quality of life in COPD patients 142 . In line with this, Mukerji et al 143 .…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 90%
“… 28 , 30 , 38 , 136 , 137 , 138 , 139 , 140 , 141 It has been demonstrated that COPD severity was associated with serum Mg 2+ deficiency and a worse quality of life in COPD patients. 142 In line with this, Mukerji et al. 143 demonstrated that intravenous adjuvant therapy with MgSO 4 improves bronchodilator therapy in acute exacerbations of COPD.…”
Section: Magnesium Consumption During Covid‐19 and Post‐covid‐19 Diseasementioning
confidence: 91%
“…Patients with COPD generally have higher smoking status and lower lung function, and these factors were found to be associated with HR-QOL scores. 21) These results suggested that the influence of vitamin D status on HR-QOL score was relatively limited compared to the clinical features of COPD. Our results support the findings of previous cross-sectional studies which did not find associations between vitamin D status and general and COPDspecific HR-QOL scores, including EQ-5D scores and the St. George's Respiratory Questionnaire, in COPD patients.…”
Section: Discussionmentioning
confidence: 92%